3D-printed graphene polylactic acid devices resistant to SARS-CoV-2: Sunlight-mediated sterilization of additive manufactured objects. (July 2022) - De Maio, Flavio; Rosa, Enrico; Perini, Giordano; Augello, Alberto; Niccolini, Benedetta; Ciaiola, Francesca; Santarelli, Giulia; Sciandra, Francesca; Bozzi, Manuela; Sanguinetti, Maurizio; Sali, Michela; De Spirito, Marco; et al.
Abstract: Additive manufacturing has played a crucial role in the COVID-19 global emergency allowing for rapid production of medical devices, indispensable tools for hospitals, or personal protection equipment. However, medical devices, especially in nosocomial environments, represent high touch surfaces prone to viral infection and currently used filaments for 3D printing can't inhibit transmission of virus [1]. Graphene-family materials are capable of reinforcing mechanical, optical and thermal properties of 3D printed constructs. In particular, graphene can adsorb near-infrared light with high efficiency. Here we demonstrate that the addition of graphene nanoplatelets to PLA filaments (PLA-G) allows the creation of 3D-printed devices that can be sterilized by near-infrared light exposure at power density analog to sunlight. This method has been used to kill SARS-CoV-2 viral particles on the surface of 3D printed PLA-G by 3 min of exposure. 3D-printed PLA-G is highly biocompatible and can represent the ideal material for the production of sterilizable personal protective equipment and daily life objects intended for multiple users. Graphical abstract: Image 1